2003
DOI: 10.1071/fp03093
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa nodulation by Sinorhizobium fredii does not require sulfated Nod-factors

Abstract: Rhizobium strain 042B(s) is able to nodulate both soybean and alfalfa cultivars. We have demonstrated, by mass spectrometry, that the nodulation (Nod) factors produced by this strain are characteristic of those produced by Sinorhizobium fredii, which typically nodulates soybean; they have 3–5 N-acetylglucosamine (GlcNAc) residues, a mono-unsaturated or saturated C16, C18 or C20 fatty-acyl chain, and a (methyl)fucosyl residue on C6 of the reducing-terminal GlcNAc. In order to study Rhizobium strain 042B(s) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Nar and Kae have been demonstrated as nod gene inducers of many rhizobia, for instance, B. japonicum, Bradyrhizobium sp. strain ORS285, Sinorhizobium fredii and Rhizobium leguminosarum (Kosslak et al, 1987;Begum et al, 2001;Noreen et al, 2003;Renier et al, 2011), and a mixtures of flavonoids is more effective in inducing nod genes in comparison to a single flavonoid (Cooper, 2004;Hassan & Mathesius, 2012). Consistently, nodD1 of B. japonicum and B. elkanii was also induced during cocultivation with Ph, suggesting that Ph-mediated nod genes induction occurred in many types of rhizobium.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nar and Kae have been demonstrated as nod gene inducers of many rhizobia, for instance, B. japonicum, Bradyrhizobium sp. strain ORS285, Sinorhizobium fredii and Rhizobium leguminosarum (Kosslak et al, 1987;Begum et al, 2001;Noreen et al, 2003;Renier et al, 2011), and a mixtures of flavonoids is more effective in inducing nod genes in comparison to a single flavonoid (Cooper, 2004;Hassan & Mathesius, 2012). Consistently, nodD1 of B. japonicum and B. elkanii was also induced during cocultivation with Ph, suggesting that Ph-mediated nod genes induction occurred in many types of rhizobium.…”
Section: Discussionmentioning
confidence: 78%
“…japonicum , Bradyrhizobium sp. strain ORS285, Sinorhizobium fredii and Rhizobium leguminosarum (Kosslak et al ., 1987; Begum et al ., 2001; Noreen et al ., 2003; Renier et al ., 2011), and a mixtures of flavonoids is more effective in inducing nod genes in comparison to a single flavonoid (Cooper, 2004; Hassan & Mathesius, 2012). Consistently, nodD1 of B. japonicum and B .…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that pseudonodules formed on M. sativa roots in all variants of inoculation did not contain any rhizobia ( Figure 3A–C ), although bacterial cells of the strain Ach-343 were present on the root surface ( Figure 3B ). It is known that M. sativa is a highly specific plant that forms a symbiosis only with bacteria Sinorhizobium meliloti and S. medicae , although it has been shown that some other rhizobial strains can also nodulate this plant species ( Noreen et al, 2003 ; Torres Tejerizo et al, 2011 ). In contrast, in nodules on T. pratense roots inoculated with the strains Opo-235(pMP4655) or Ach-343(pHC60) the corresponding bacteria were present ( Figure 3D,E ), while in the variant of co-inoculation only nodules with the strain Opo-235(pMP4655) were observed ( Figure 3F ).…”
Section: Resultsmentioning
confidence: 99%
“…In alfalfa, the expression of nodulin gene MtENOD12 was significantly inhibited after inoculation with a nodH mutant compared to the wild-type Rhizobium meliloti , suggesting the sulfated Nod factors are required for nodulation by R. meliloti [ 29 ]. However, alfalfa nodulation by Sinorhizobium fredii does not required sulfated Nod-factors [ 30 ].…”
Section: Discussionmentioning
confidence: 99%